ASSESSMENT OF ICT USAGE IN ESTATE SURVEYING AND VALUATION PRACTICE IN NIGERIA - Adedamola Akinola, Wasiu; Oyewale Oyedeji, Joseph; Funmilayo Faturoti, Toyin (International Journal of Property Sciences (E-ISSN: 2229-8568), 2021)
To operate in a dynamic environment, the success of real estate companies’ hinges, to a large extent, on their ability to deliver innovative, user-accepted products and services in a timely, seamless manner. The need for Information and Communication Technology (ICT) for secure, safe, and adequately serviced estate surveying and valuation practice is very pertinent to the profession. Therefore, this study assessed the level of usage of ICT in estate surveying and valuation practice in the study area with the view of improving real estate service delivery in Lagos Island, Nigeria. Data were gathered through a survey conducted with registered estate firms in Lagos Island, Nigeria. The data from the responses that were gathered were analysed using descriptive statistics and Relative Importance Index (RII) ranking. Findings revealed that the majority of the respondents are adopting ICT in carrying out their estate surveying and valuation practice. In addition, the results of the study established a positive correlation between improving estate surveying practice and the adoption of ICT. Furthermore, the findings also revealed the level of conversant with the use of real estate software has the highest RII while Artificial Intelligence software has the lowest RII. The study concluded that it is without a doubt that the degree of application of ICT in real estate has been very significant, but there are still barriers that limit its application within the sector. The study recommends that the estate surveyors & valuers in academia who are responsible for coaching core departmental courses include ICT into several aspects of the curriculum.